Picture Based Insurance (PBI) in India, 2016-17 - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
This dataset serves to shed light on the feasibility of picture-based crop insurance (PBI), which is a new way of delivering affordable and easy-to-understand crop insurance, using farmers’ smartphone pictures to minimize the costs of loss verification. During the winter (Rabi) 2016-17 season, a formative evaluation of PBI in Haryana and Punjab, India invited 750 wheat producers to take regular pictures of selected wheat sites throughout the cultivation season. To make the data from this formative evaluation publicly available, we are sharing a site-level dataset (with approximate GPS coordinates, precision of ~10km, and information on yields, damage visible in the pictures as assessed by experts, and whether data triggered insurance payouts) and a picture-level dataset (with information on the timing and frequency of pictures taken, as well as approximate GPS coordinates of pictures taken, precision of ~10km).